Analisis Pengaruh Peningkatan Kerja Perawat dalam Pencegahan dan Pengendalian Infeksi dengan Pendekatan Employee Engagement - Amanda, Silvia Rizki; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to analyze the effect of increasing nurses' work in preventing and controlling infections with an employee engagement approach. The research method used a cross-sectional study. The study's results were that there was an effect of the employee engagement approach on the aspect of nurse capacity on improving the quality of nurse work in preventing and controlling infections in Medan City Private Hospitals with a p significance value of 0.000 <0.05. There was an effect of the employee engagement approach on nurse motivation in improving the quality of nurse work in preventing and controlling infections with a p-significance p-value of 0.000 <0.05. There was an effect of the employee engagement approach on nurse freedom in improving the quality of nurse work in preventing and controlling infections with a p-significance value of 0.000 <0.05. In conclusion, there was a significant influence between the capacity, motivation, and freedom of nurses on improving the quality of nurse work in preventing and controlling infections in Medan City Private Hospitals. Keywords: Infection, Nurse Work, Prevention, Control